Pengembangan Media Pembelajaran Matematika SMP Berbasis Augmented Reality dengan Nuansa Etnomatematika Ukiran Toraja - Yuda Satria Nugraha; Vaira Indah Wahyuni (Jambura Journal of Mathematics Education, 2026)
The development of digital technology in education has encouraged the need for innovative learning media that are more interactive, contextual, and aligned with students’ needs. One promising effort is the integration of Augmented Reality (AR) technology with ethnomathematics, particularly Toraja carvings, to create more meaningful mathematics learning experiences. This study aims to develop AR-based mathematics learning media incorporating the ethnomathematical nuances of Toraja carvings and to examine its validity and practicality as a supporting tool for teaching mathematics in Grade IX of junior high school. The research employed a development study using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects consisted of 150 students from six junior high schools in Palopo City, selected through purposive sampling and random sampling techniques. The development process involved curriculum analysis, exploration of Toraja carving motifs relevant to geometric transformation topics, storyboard design and interactive flow development, and the creation of an AR prototype, which was then validated by experts and tested with students. The findings revealed that the developed media achieved an average validity score of 85.42%, categorized as highly valid, and an average practicality score of 77.82%, categorized as practical. These results indicate that the media is not only feasible in terms of content and presentation but also practical for use in mathematics learning. This study provides an innovative solution to enhance students’ engagement and to foster a more contextual and meaningful learning experience.